Effect Firm Growth, Firm Size, Debt Policy on Profitability Case Study On Telecommunication Subsector Listed On BEI - Samara, Aldi; Wijaya, Anton; Susanti, Metta; Suhendri, Suhendri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to determine the effect of company growth, company size, debt policy on case profitability studies of telecommunications companies listed on the Indonesia Stock Exchange either simultaneously or partially. The population in this research is a case study of the telecommunication sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period as many as 6 companies. Hypothesis testing in this study was carried out using the Smart PLS (Partial Least Square) program. Based on the analysis of the magnitude of the influence obtained for the percentage of influence of Company Size is the most dominant influence of other variables with a percentage of 48.3575% while the variable growth of the Company is only able to influence the variable Profitability of 6%. And the Debt Policy variable only affects the Profitability variable by -1%. For Variable Growth, Company Size, Debt Policy on Profitability of 53.36%.